High-density flaky powder magnetic powder core material and preparation method thereof
By applying binder coating and magnetic field rotation orientation treatment to the sheet magnetic powder particles, combined with molding and heat treatment, the problem of difficult to prepare the sheet magnetic powder core material into a high density structure is solved, and a high-performance magnetic powder core material is achieved.
Patent Information
- Application Number
- CN202411735432.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The sheet-shaped powder magnetic powder core material is difficult to prepare into a high-density structure, resulting in degradation of performance, including low magnetic permeability, low saturation magnetization and high loss.
Flake-shaped magnetic powder particles with a diameter-thickness ratio of not less than 10 are used to coat binder and rotate the magnetic field, followed by molding and heat treatment to achieve a high density magnetic powder core material.
The sheet-shaped powder magnetic powder core prepared by this method has high magnetic permeability, high operating frequency, high saturation magnetization, high mechanical strength and low loss, solving the problem that high density structure is difficult to achieve.
Smart Images

Figure CN119560292A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metallic soft magnetic materials, and in particular to a high-density flaky powder magnetic core material and a preparation method thereof. Background Art
[0002] In recent years, magnetic powder core materials (SMCs) have been widely used in new industries such as new energy vehicles, photovoltaic power generation, wind power generation, and big data centers, and have become the hottest new soft magnetic materials in recent years. This material not only inherits the advantages of high saturation flux density of metal soft magnetic materials, but also the tiny magnetic powder particle size and surface insulation effectively suppress the eddy current effect of the material. Therefore, this material is a soft magnetic material with comprehensive advantages such as high saturation flux density, high DC bias, high Curie temperature, high application frequency band and low loss, which is perfectly adapted to the current development needs of electronic devices towards miniaturization, high frequency, high power, and high reliability.
[0003] Compared with other bulk metal soft magnetic materials and ferrite soft magnetic materials, magnetic powder core materials have a strong demagnetization field inside, which leads to a lower magnetic permeability of metal magnetic powder cores. The magnetic permeabilities of commercial metal magnetic powder core materials are currently only 29, 60, and 90. Reducing the demagnetization field by using flaky particles with a high aspect ratio has become the simplest and most effective way to increase the magnetic permeability of metal soft magnetic powder cores. The Che Shenglei research group at Zhejiang University of Technology has shown in experiments that the magnetic permeability of magnetic powder core materials prepared using flaky FeSiAl magnetic powder particles with a high aspect ratio can be increased by about 10 times compared to traditional FeSiAl magnetic powder cores.
[0004] Although the magnetic cores filled with flaky magnetic powder have the advantages of high magnetic permeability and wider application bandwidth compared to traditional spherical powder and crushed powder; however, due to the significantly increased specific surface area of flaky magnetic powder particles and the difficulty in achieving a close-packed stacking structure through slip during the molding process, it is difficult to achieve a high-density structure for the magnetic powder core materials prepared from them, which greatly reduces their performance.
[0005] At present, the preparation methods of flaky magnetic powder mainly include tape casting and lamination. Among them, the tape casting method requires the addition of a large amount of binder in the process of preparing flaky powder samples, which leads to low density, low magnetic permeability, low saturation magnetization, high loss and poor mechanical properties of the samples prepared by the tape casting method. Although the lamination method can prepare high-density flaky samples, the lamination method is greatly affected by the external environment during the preparation of samples. For example, the flaky magnetic powder is often used as a soft magnetic material such as an absorber. The proportion of binder in the preparation process of the flaky FeSiAl absorber is not less than 15 wt.% of the magnetic powder, and the density of the corresponding absorber is often not more than 4 g / cm 3The introduction of too much binder reduces the density of the magnetic powder core. On the one hand, this state will reduce the composition of the magnetic material in the magnetic powder core, thereby reducing the saturation magnetization intensity, magnetic permeability and loss of the magnetic powder core; on the other hand, it will hinder the heat treatment of the magnetic powder core and make it impossible to further optimize its performance.
[0006] Therefore, how to solve the problem that flaky powder cannot be prepared into high density has become the key point to improve the performance of flaky powder cores. Summary of the invention
[0007] One of the purposes of the present invention is to provide a method for preparing a high-density flaky magnetic powder core material to solve the above-mentioned problem.
[0008] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: a method for preparing a high-density flaky powder magnetic powder core material, using flaky magnetic powder particles with a diameter-to-thickness ratio of not less than 10 as raw materials, firstly coating the flaky magnetic powder particles with a binder, then subjecting the coated material to a magnetic field rotation orientation treatment, and then subjecting the material to molding and heat treatment to obtain the material.
[0009] As a preferred technical solution, the raw material flaky magnetic powder particles are selected from one of FeSiAl, FeSiCr, FeSi, FeNi, FeNiMo, and carbonyl iron.
[0010] As a preferred technical solution, the binder coating method is to mix the raw flaky magnetic powder particles and the binder, add them to a solvent corresponding to the binder, and disperse and mix them under ultrasonic conditions; then, grind the mixed liquid of magnetic powder particles-binder-solvent until the solvent evaporates completely, and then add a lubricant thereto.
[0011] As a further preferred technical solution, the adhesive is selected from at least one of silicone resin, polyvinyl alcohol, polyurethane, and phenolic resin, the solvent is selected from acetone or alcohol, and the lubricant is a zinc stearate lubricant.
[0012] As a preferred technical solution, the magnetic field rotation orientation treatment is carried out in a magnetic field rotation orientation device, which includes an orientation mold, an external magnetic field and a rotating device, wherein: The orientation mold is made of non-magnetic material. The shape of the orientation mold depends on the shape of the magnetic powder core to be prepared. For example, the magnetic powder core prepared in one embodiment of the present invention is a ring-shaped magnetic powder core. The orientation mold is mainly composed of an outer ring, a central axis, a base and a capping cover. When making magnetic cores with other shapes, corresponding adjustments need to be made. The role of the orientation mold is to serve as a container for the flaky magnetic powder so that it can be affected by the magnetic field in the magnetic field, thereby controlling the arrangement of the flaky powder. At the same time, the mold can limit the flaky magnetic powder so that it will not be adsorbed to the magnetic pole due to the action of the magnetic field. The external magnetic field is composed of a pair of N and S magnetic poles, which are placed opposite to each other, aiming to generate a uniform magnetic field perpendicular to the magnetic pole surface and with an intensity of about 0.1-0.5T between the two magnetic poles. In the present invention, the role of the magnetic field is to arrange the sheet-shaped magnetic powder in the same plane, so the magnitude of the magnetic field intensity has little effect; The rotating device is composed of a motor and a non-magnetic transmission rod located at the bottom. The motor at the bottom drives the orientation mold to rotate in the magnetic field through the non-magnetic transmission rod, thereby achieving the purpose of rotating magnetic field orientation. The rotation speed is 1 to 60 revolutions per minute. The rotating device here is to make the flaky magnetic powder evenly stressed, so the rotation orientation time and rotation speed have no obvious effect on the magnetic powder core.
[0013] The magnetic field rotation orientation of the present invention is completed by the above-mentioned magnetic field orientation equipment; the method for performing magnetic field rotation orientation can be: loading the magnetic powder to be oriented into the orientation mold, then placing the orientation mold containing the flaky magnetic powder in the magnetic field, starting the motor to make the orientation mold containing the magnetic powder rotate and orient for 3 minutes in a magnetic field of about 0.3T, thereby completing the magnetic field rotation orientation.
[0014] As a preferred technical solution, the heat treatment method is: heat treatment is performed in a nitrogen atmosphere for 15 to 120 minutes at a temperature of 500 to 750°C.
[0015] The second object of the present invention is to provide a high-density flaky powder magnetic core material prepared by the above method.
[0016] The inventors of the present application have found through a large number of experiments that the main reason why flaky powder magnetic powder cores are difficult to be pressed into high density is due to the disordered accumulation of flaky powder particles; the disordered flaky magnetic powder particles will not slip and slightly deform under external pressure like spherical particles to form a close-packed structure, but will undergo elastic deformation phenomena such as bending. When the external pressure is removed, the deformed particles will destroy the close-packed state of the magnetic powder core, causing the magnetic powder core to break. Therefore, solving the problem of disordered arrangement of magnetic powder particles is the key to the molding of flaky powder magnetic powder cores.
[0017] The present invention introduces a magnetic field rotation orientation link during the forming process of the flaky magnetic powder core material, thereby adjusting the arrangement of tiny flaky magnetic powder particles, so that all magnetic powder particles are stacked in parallel and closely packed, and further pressed into a magnetic powder core with a high-density structure.
[0018] Compared with the prior art, the advantages of the present invention are: the present invention solves the problem of difficulty in molding high-density flaky magnetic powder filled magnetic powder cores, and the flaky powder magnetic powder cores prepared by this method have the advantages of high magnetic permeability, high operating frequency, high saturation magnetization intensity, high mechanical strength and low loss. This method provides a key technology for the development of high-density flaky powder magnetic powder cores. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a structural diagram of the magnetic field orientation device in the present invention; Figure 2 The electron microscope image of the microscopic morphology of the low-diameter thick-flaky FeSiAl magnetic powder particles used in Comparative Example 1; Figure 3 The magnetic spectrum of the low aspect ratio flaky FeSiAl magnetic powder core prepared in Comparative Example 1 in the frequency range of 1 MHz to 1 GHz; Figure 4 The loss curve per unit volume of the low-diameter-to-thickness ratio flaky FeSiAl magnetic powder core prepared in Comparative Example 1 in the frequency range of 20 to 1000 kHz at a magnetic flux density of 100 mT; Figure 5 Figure a is an electron microscope image of the microscopic morphology of the flaky FeSiAl magnetic powder particles with a high aspect ratio used in Example 1. Figure 5 b is a microscopic cross-sectional view of the flaky FeSiAl magnetic powder core prepared in Example 1; Figure 6 The magnetic spectrum of the high aspect ratio lamellar FeSiAl magnetic powder core prepared in Implementation 1 in the frequency range of 1 MHz to 1 GHz; Figure 7 The dynamic hysteresis loop of the FeSiAl magnetic powder core prepared in Example 1 under an external field of 5kHz and 6500A / m; Figure 8 The loss curve per unit volume of the FeSiAl magnetic powder core prepared in Comparative Example 1 at a frequency of 20 to 1000 kHz and a magnetic flux density of 100 mT; Fig. 9 Figure a is an electron microscope image of the microscopic morphology of the flaky FeSi6.5 magnetic powder particles used in Example 2; Fig. 9 b is a microscopic cross-sectional view of the flaky FeSi6.5 magnetic powder core prepared in Example 2; Fig.10 The magnetic spectrum of the FeSi6.5 flaky magnetic powder core prepared in Example 2 in the frequency range of 1 MHz to 1 GHz; Fig.11 The dynamic hysteresis loop of the FeSi6.5 magnetic powder core prepared in Example 2 under an external field of 5kHz and 25000A / m; Fig.12Fig. a is an electron microscope image of the microscopic morphology of the flaky FeSiCr magnetic powder particles used in Example 3; Fig.12 b is a microscopic cross-sectional view of the flaky FeSiCr magnetic powder core prepared in Example 3; Fig.13 The magnetic spectrum of the FeSiCr magnetic powder core prepared in Example 3 from 1 MHz to 1 GHz; Fig.14 This is the dynamic hysteresis loop of the FeSiCr magnetic powder core prepared in Example 3 under 5kHz and 10000A / m external field. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with the accompanying drawings. Example
[0021] A method for preparing a high-density flaky FeSiAl magnetic powder core comprises the following steps: a) Weigh 30g of FeSiAl flaky magnetic powder (such as Figure 5 a), 0.45g of Ren60 and 0.1g of zinc stearate; b) adding FeSiAl magnetic powder and Ren60 into acetone solvent and dispersing and mixing them under ultrasonic conditions; after 5 minutes, pouring the FeSiAl magnetic powder / Ren60 / acetone mixture into a grinding cymbal and grinding it for 30 minutes until the acetone is completely evaporated, and then adding zinc stearate thereto, thereby completing the work of coating the flaky FeSiAl magnetic powder particles with the binder; c) Take the FeSiAl magnetic powder coated with binder in step b) to Figure 1 The orientation mold is shown and placed Figure 1 The magnetic field orientation device shown performs magnetic field rotation orientation processing; d) placing the FeSiAl magnetic powder subjected to the magnetic field orientation treatment in step c) in a press, and performing a molding process on the FeSiAl magnetic powder at a pressure of 1800 MPa to obtain a flaky FeSiAl-filled magnetic powder core; e) placing the FeSiAl magnetic powder core obtained in step d) in an atmosphere furnace, heating it for 90 minutes and heat treating it at 750° C. for 60 minutes under a nitrogen atmosphere; When the furnace temperature naturally cools down to room temperature, the flaky FeSiAl magnetic powder core is taken out and its performance is tested.
[0022] in, Figure 1The magnetic field orientation device comprises an orientation mold, an external magnetic field and a rotating device, wherein the orientation mold is composed of an outer ring 1, a central axis 2, a base 3 and a capping cover 4; the external magnetic field is composed of a pair of N and S magnetic poles 5, and the two magnetic poles are placed opposite to each other; the rotating device is composed of a motor 6 and a non-magnetic transmission rod 7 located at the bottom; Depend on Figure 5 Figure a shows the microscopic morphology of the flaky FeSiAl magnetic powder particles used in this embodiment. The particle size D50 of the flaky FeSiAl magnetic powder is 124 μm, which is a large-diameter flaky particle, and the diameter-to-thickness ratio is far greater than 10. Figure 5 Figure b shows a microscopic cross-sectional view of the flaky FeSiAl magnetic powder core prepared by magnetic field rotation orientation. The flaky magnetic powder particles inside the FeSiAl magnetic powder core prepared in this embodiment are neatly arranged in the same plane. This method achieves the orderly arrangement of the flaky FeSiAl magnetic powder particles, thereby preparing a ferrite with a density of 6.1 g / cm 3 The density of the flaky FeSiAl magnetic powder core is 90% of the density of the FeSiAl alloy, reaching the density level of the spherical FeSiAl magnetic powder core, which means that the preparation of high-density flaky FeSiAl magnetic powder core material is achieved through this method; Depend on Figure 6 It can be seen from the magnetic spectrum of the high-density flaky FeSiAl magnetic powder core that the magnetic permeability of the flaky FeSiAl magnetic powder core reaches 1160 at 1MHz, and the magnetic permeability can be flattened to 1.5MHz; the flaky FeSiAl magnetic powder core of this embodiment successfully achieves heat treatment while maintaining high density, resulting in the magnetic permeability of the magnetic powder core reaching 1160; Depend on Figure 7 It can be seen that the dynamic hysteresis loop of the high-density flaky FeSiAl magnetic powder core reaches a magnetic induction intensity of 0.83T under magnetization at 5kHz and 6500A / m external field; the high density means that the magnetic components inside the flaky FeSiAl magnetic powder core account for a high proportion, and the magnetic powder core reaches a high magnetic induction intensity, which exceeds the saturation magnetization intensity of all known ferrites.
[0023] Depend on Figure 8 It can be seen that the loss of the high-density flaky FeSiAl magnetic powder core varies with frequency. The loss of the high-density flaky FeSiAl magnetic powder core is about 11000 at 1MHz and 100mT, which is half of the loss of the FeSiAl magnetic powder core in Comparative Example 1.
[0024] Comparative Example 1 This comparative example is a method for preparing a low-diameter-to-thickness ratio flaky FeSiAl magnetic powder core, which comprises the following steps: a) Weigh 30g of FeSiAl flaky magnetic powder (such as Figure 2), 0.45 g of silicone resin (WACKER Ren60, hereinafter referred to as "Ren60") and 0.1 g of zinc stearate; b) adding FeSiAl magnetic powder and Ren60 into acetone solvent and dispersing and mixing them under ultrasonic conditions; after 5 minutes, pouring the FeSiAl magnetic powder / Ren60 / acetone mixture into a grinding cymbal and grinding it for 30 minutes until the acetone is completely evaporated, and then adding zinc stearate thereto, thereby completing the work of coating the flaky FeSiAl magnetic powder particles with the binder; c) placing the FeSiAl magnetic powder prepared in step b) in a press, and subjecting the FeSiAl magnetic powder to a molding process at a pressure of 1800 MPa to obtain a flaky FeSiAl-filled magnetic powder core; d) placing the FeSiAl magnetic powder core obtained in step c) in an atmosphere furnace, heating it for 90 minutes and heat treating it at 750° C. for 60 minutes under a nitrogen atmosphere; When the furnace temperature naturally cools down to room temperature, the flaky FeSiAl magnetic powder core is taken out and its performance is tested.
[0025] Depend on Figure 2 As can be seen from the microscopic morphology of the flaky FeSiAl magnetic powder particles used in this embodiment, the thickness of the flaky FeSiAl is about 5 μm, and the D50 is 40 μm, so the diameter-to-thickness ratio of the magnetic powder does not exceed 10; the density of the prepared FeSiAl magnetic powder core is 4.1 g / cm 3 , the density of FeSiAl alloy is about 6.8g / cm 3 , the density of the magnetic powder core prepared by direct pressing is 60% of the density of FeSiAl alloy; Depend on Figure 3 It can be seen that the magnetic spectrum of the low-diameter-to-thickness ratio flaky FeSiAl magnetic powder core has a magnetic permeability of 130 at 1MHz; Depend on Figure 4 It can be seen that the loss of the low aspect ratio FeSiAl magnetic powder core varies with frequency. The loss of the low aspect ratio FeSiAl magnetic powder core is about 22600 at 1MHz and 100mT. Example
[0026] A method for preparing a high-density flaky FeSi6.5 magnetic powder core comprises the following steps: a) Weigh 30g of FeSi6.5 flaky magnetic powder (such as Fig. 9 a), 0.45g Ren60 and 0.1g zinc stearate; b) Add FeSi6.5 magnetic powder and Ren60 into acetone solvent and disperse and mix them under ultrasonic conditions. After 5 minutes, pour the FeSi6.5 magnetic powder / Ren60 / acetone mixture into a grinding cymbal and grind it for 30 minutes until the acetone evaporates completely. Then, add zinc stearate to complete the work of coating the flaky FeSi6.5 magnetic powder particles with the binder. c) Take the FeSi6.5 magnetic powder coated with binder in step b) to Figure 1 The orientation mold is shown and placed Figure 1 The magnetic field orientation device shown performs magnetic field rotation orientation processing; d) placing the FeSi6.5 magnetic powder subjected to the magnetic field rotation orientation treatment in step c) in a press, and performing a molding process on the magnetic powder at a pressure of 1800 MPa to obtain a flaky FeSi6.5 filled magnetic powder core; e) placing the FeSi6.5 magnetic powder core obtained in step d) in an atmosphere furnace, heating it for 90 minutes and heat treating it at 750° C. for 60 minutes under a nitrogen atmosphere; When the furnace temperature naturally cools down to room temperature, take out the FeSi6.5 magnetic powder core and test its performance.
[0027] Depend on Fig. 9 a It can be seen from the microscopic morphology of the flaky FeSi6.5 magnetic powder particles used in this embodiment that the particle size D50 of the flaky FeSi6.5 magnetic powder is 123 μm, which is a large-diameter flaky particle, and the diameter-to-thickness ratio is far greater than 10; Fig. 9 b shows the microscopic cross-section of the flaky FeSi6.5 magnetic powder core prepared by magnetic field rotation orientation. The flaky magnetic powder particles inside the FeSi6.5 magnetic powder core prepared in this embodiment are neatly arranged in the same plane. This process achieves the orderly arrangement of the flaky FeSi6.5 magnetic powder particles, thereby preparing a ferrite with a density of 6.8 g / cm 3 The density of FeSi6.5 alloy is about 7.4g / cm 3 The density of the flaky FeSi6.5 magnetic powder core is 90% of the density of the FeSi6.5 alloy and reaches the density level of the spherical FeSi6.5 magnetic powder core, which means that the preparation of high-density flaky FeSi6.5 magnetic powder core material is achieved through this method; Depend on Fig.10 It can be seen from the magnetic spectrum of the high-density FeSi6.5 powder core that the permeability of the FeSi6.5 powder core is 120 at 1MHz, and the permeability can be flattened to 15MHz; Depend on Fig.11It can be seen that the dynamic hysteresis loop of the high-density flaky FeSi6.5 magnetic powder core reaches a magnetic induction intensity of 1.43T under magnetization at 5kHz and 25000A / m external field. The high density enables the flaky FeSi6.5 magnetic powder core to reach a high magnetic induction intensity value. Example
[0028] A method for preparing a high-density flaky FeSiCr magnetic powder core comprises the following steps: a) Weigh 30g of FeSiCr flaky magnetic powder (such as Fig.12 a), 0.6 g Ren60, 0.1 g zinc stearate; b) adding FeSiCr magnetic powder and Ren60 into acetone solvent and dispersing and mixing them under ultrasonic conditions, and after 5 minutes, pouring the magnetic powder / Ren60 / acetone mixture into a grinding cymbal and grinding for 30 minutes until the acetone is completely evaporated, and then adding zinc stearate thereto, thereby completing the preparation of binder-coated flaky FeSiCr magnetic powder particles; c) Take the FeSiCr magnetic powder coated with binder in step b) to Figure 1 The orientation mold is shown and placed Figure 1 The magnetic field orientation device shown performs magnetic field rotation orientation processing; d) placing the flaky FeSiCr magnetic powder subjected to the magnetic field orientation treatment in step c) in a press, and performing a molding process on the magnetic powder at a pressure of 1800 MPa to obtain a flaky FeSiCr-filled magnetic powder core; e) placing the magnetic powder core obtained in step d) in an atmosphere furnace, and performing a heat treatment at 750° C. for 60 minutes under a nitrogen atmosphere for a period of 90 minutes; When the furnace temperature is cooled naturally to room temperature, the FeSiCr magnetic powder core is taken out and its performance is tested; Depend on Fig.12 a It can be seen from the microscopic morphology of the flaky FeSiCr magnetic powder particles used in Example 3 that the D50 of the flaky FeSiCr magnetic powder particle size is 74 μm, and the diameter-to-thickness ratio of the FeSiCr magnetic powder particles is much greater than 10; and Fig.12 b shows the microscopic cross-sectional view of the flaky FeSiCr magnetic powder core prepared by magnetic field orientation in this embodiment. The flaky magnetic powder particles inside the FeSiCr magnetic powder core prepared in this embodiment are neatly arranged in the same plane. This process realizes the orderly arrangement of the flaky FeSiCr magnetic powder, thereby preparing a 5.6 g / cm 3 High-density FeSiCr powder core. The density of FeSiCr alloy is about 6.0g / cm 3The density of the flaky FeSiCr magnetic powder core is 93% of the density of the blocky FeSiCr alloy, which has reached the level of the spherical FeSiCr magnetic powder core. This means that the preparation of high-density flaky FeSiCr magnetic powder core materials has been achieved through this method. Depend on Fig.13 It can be seen from the magnetic spectrum of the high-density FeSiCr powder core that the permeability of the FeSiCr powder core is 60 at 1MHz, and the permeability can be flat to 50MHz; Depend on Fig.14 It can be seen that the dynamic hysteresis loop of the high-density FeSiCr magnetic powder core reaches a magnetic induction intensity of 0.63T under 5kHz and 10000A / m external field magnetization.
[0029] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-density flaky magnetic powder core material, characterized in that: The flaky magnetic powder particles with a diameter-to-thickness ratio of not less than 10 are used as raw materials, the flaky magnetic powder particles are firstly coated with a binder, and then the coated material is subjected to a magnetic field rotation orientation treatment, and then molding and heat treatment are performed to obtain the obtained material.
2. The method according to claim 1, characterized in that The raw material flaky magnetic powder particles are selected from one of FeSiAl, FeSiCr, FeSi, FeNi, FeNiMo and carbonyl iron.
3. The method according to claim 1, characterized in that The binder coating method is to mix the raw material flaky magnetic powder particles and the binder, add them into a solvent corresponding to the binder, and disperse and mix them under ultrasonic conditions; then, grind the mixed liquid of the magnetic powder particles-binder-solvent until the solvent evaporates completely, and then add a lubricant thereto.
4. The method according to claim 1, characterized in that The adhesive is selected from at least one of silicone resin, polyvinyl alcohol, polyurethane and phenolic resin, the solvent is selected from acetone or alcohol, and the lubricant is a zinc stearate lubricant.
5. The method according to claim 1, characterized in that The magnetic field rotation orientation treatment is carried out in a magnetic field rotation orientation device, which includes an orientation mold, an external magnetic field and a rotating device, wherein the orientation mold is made of non-magnetic material, and the morphology of the orientation mold depends on the morphology of the prepared magnetic powder core; the external magnetic field is composed of a pair of N and S magnetic poles, and the two magnetic poles are placed opposite each other; the rotating device is composed of a motor located at the bottom and a non-magnetic transmission rod.
6. The method according to claim 1, characterized in that The heat treatment method is: heat treatment is performed in a nitrogen atmosphere for 15 to 120 minutes at a temperature of 500 to 750°C.
7. A high-density flaky powder magnetic core material prepared by the method according to any one of claims 1 to 6.